STUDI PERBANDINGAN SISTEM PENDIDIKAN DI INDONESIA DENGAN MALAYSIA - Devi Ristyana Puji Lestari; Nurul Istiq’faroh; Hitta Alfi Muhimmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research compares the education systems in Indonesia and Malaysia using a literature review study method. The main objective of this research is to identify differences in curriculum structure, teaching methods, educational policies, student outcomes, challenges and opportunities, as well as the implementation of educational policies during the COVID-19 pandemic in the two countries. The research results show that Indonesia applies the 2013 Curriculum (K-13) which emphasizes developing student competencies in aspects of knowledge, skills and attitudes, while Malaysia uses the National Curriculum which focuses on mastery of Malay, English, science, mathematics and moral education. and citizenship. Teaching methods in Indonesia vary and technology is starting to be implemented in urban schools, while Malaysia is more advanced in the integration of educational technology and 21st Century Learning approaches. Education policy in Indonesia includes a 12-year compulsory education program and School Operational Assistance (BOS), while Malaysia implements 11 year compulsory education program and Malaysia Education Blueprint 2015-2025. Student achievements in national exams and international tests such as PISA show that both countries still need to improve the quality of their education. The main challenge in Indonesia is the gap in education quality between urban and rural areas and limited facilities, while Malaysia faces the challenge of the gap between urban and rural schools as well as differences in quality between national schools and types of nationality. The COVID-19 pandemic forced both countries to adopt distance learning, with various obstacles and solutions being implemented. In conclusion, although there are many challenges, there are also great opportunities to improve the quality of education in Indonesia and Malaysia through appropriate policies, innovation in teaching methods, and the use of technology. Keywords: comparison of education systems, indonesian education system, malaysian education system